Application of Ultimum Remedium Principles in Progressive Law Perspective - Abdurrachman, Hamidah; Hamzani, Achmad Irwan; Sudewo, Fajar Ari; Aravik, Havis; Khasanah, Nur (International Journal of Criminology and Sociology, 2021)
Ultimum remedium is one of the principles contained in Indonesian criminal law which says that criminal law should be made a final effort in the case of law enforcement. However, law enforcement through the criminal justice system is currently still dominated by the positivism mindset, a way of (criminal) law enforcement which is only based on laws and regulations. In many cases, Criminal Law is used as the only way of order. The purpose of this research is to describe the concept of Ultimum remedium in criminal law, criminal law enforcement practices in Indonesia, and criminal law enforcement concepts in the progressive law paradigm. This research used a philosophical approach discussing law enforcement idealism in the future. The data used were the qualitatively analyzed secondary data. The research results showed that the Ultimum remedium principle has not been completely implemented in law enforcement. Consequently, the burden for crime settlements got bigger and made the law enforcers busier. The Ultimum remedium principle is supported by various considering bases or grounds from the constitutional law aspect, political science, criminal law, and humanism consideration or human rights. Law enforcement in Indonesia was viewed as stagnant and discriminative law enforcement. It was illustrated as a spider web that can only trap the weak but will be easily torn by the rich and strong. Factors inhibiting law enforcement in Indonesia include weak political will and political action of the state leaders to make law as the commander. The regulations and laws reflect the political interests of authorities more than those of the society. Thus, criminal law enforcement is greatly necessary for the progressive law paradigm. Progressivity is greatly required in law enforcement. Progressive law departs from the humanistic perspective. Thinking progressively means having the courage to get out from the law absolutism thinking mainstream and positioning law in the relative position located in the entire humanistic problems.